Higher Education Students’ Use and Continuous Intention to Use Generative AI: A Systematic Literature Review - Pranoto, Velicia Marveline; Lisana (Jurnal Locus Penelitian dan Pengabdian, 2026)
This systematic literature review aims to examine existing studies on higher education students’ use and continuous intention to use generative AI to support their studies. Using PICOTQ to build the research question, as well as establish inclusion and exclusion criteria. PRISMA framework was used for the selection process. From 33 records, it was found that most studies were conducted in 2024. China was the country with most studies about generative AI. Most study populations were university students. The generative AI tool most frequently examined was ChatGPT. Most papers employed the UTAUT framework, and the most used factor in the studies was perceived usefulness. Future research should explore relevant moderators, and consider diverse student populations and generative AI tools beyond ChatGPT.